Pengaruh Kepemimpinan Spiritual Terhadap Kinerja Karyawan Pada PT. Ciputra International Proyek City of Blessing Citraland Manado - Jani Y. Rondonuwu; William A. Areros; Sofia A. P. Sambul (Universitas Sam Ratulangi, 2017)
This study aims to see whether there is influence between spiritual leadership on employee performance, especially at the company PT. Ciputra International Project City Of Blessing Citraland Manado. where the respondents in the company amounted to 49 people, who are employees of the company. and in this study, researchers get a singnifikan result where there is a strong influence between spiritual leadership and employee performance. this study is excellent as a recommendation to the company to maintain the values of spiritual leadership for its employees to be applied, especially for employee. According to (Chopra, 2002) leadership and also spiritrualitas have a huge influence on the Organization as a whole. This research use descriptive quantitative research methods by using the correlation coefficient analysis approach. Then, the results of this research were obtained that support of existing theories, namely the spiritual leadership of the significant effect on the performance of employees. In conclusion, based on the results of research that the degree of spiritual leadership influence on performance of employees at PT. Ciputra International Project of the City of Manado Citraland Blessing are included in the category is strong where it is demonstrated by the results of the correlation coefficient or r = 0.798 or 79.8%. and advice to researchers next expected to be able to improve this independent variable research more deeply, through the selection of the place of proper research and research methods that are different or the same.Keywords: Spiritual Leadership, Employee Performance